NORSE MYTHOLOGY IN M.L. KISERâ€™S â€œTREE OF LIFEâ€ - Bertha Praditya Octofani; Rr. Arielia Yustisiana (Humaniora Scientia, 2020)
This research discussed the depiction of Norse mythology and personification in M.L. Kiserâ€™sâ€œTree of Lifeâ€. The aims of this research were to give a depiction of the Norse mythologyabout tree of life and to analyze the personification dealing with mother nature of Norsemythology in M.L. Kiserâ€™s â€œTree of Lifeâ€. In finding the data, library research was appliedas the technique of collecting the data. The data consisted of ideas related to Yggdrasil innorse mythology and personification that were depicted in M.L. Kiserâ€™s poem. The theory ofmythology, Norse mythology, Norse legend of the tree of world, humanity, mother andpersonification were applied in this research. Furthermore, the approach that were usedwere mythological approach, ideological approach, archetypal approach, structuralapproach, and formalist approach. The result of this research was the whole stanza tellingthe act of Yggdrasil from the beginning of the world until the world fell into two contradictivesides. Moreover, it also told the act of Yggdrasil as a mother who took care of her children.In conclusion, by analyzing this poem, the researcher knows that Yggdrasil as the tree of lifegave life to all over the creatures.